CRITICAL DISCOURSE ANALYSIS “US CALLS CHINA, RUSSIA, IRAN, N. KOREA 'MORALLY REPREHENSIBLE' ON RIGHTS” THE JAKARTA GLOBE (APPLYING THE VAN DIJK THEORY IN MASS MEDIA) - Nurlaila Sari Harahap; Syahron Syahron; Dhara Ayu Paramitha; Muhammad Ali Sakti Nasution; Khairani Wahidah; Ridzky Hidayani; Felicia Bernadeth Simanjuntak (Universitas Negeri Padang, 2018)
The formulation of this research problem is how to analyze the daily Jakarta Globe